13Carbon mixed triglyceride breath test and pancreatic enzyme supplementation in cystic fibrosis. Issue 4 (1st April 1997) - Amarri, S; Harding, M; Coward, W A; Evans, T J; Weaver, L T
Abstract : Children with cystic fibrosis have variable degrees of exocrine pancreatic insufficiency which, if untreated, is the main cause of fat malabsorption. The impact of pancreatic enzyme supplementation on fat digestion was measured in 41 children with cystic fibrosis, 11 healthy controls, and five children with mucosal diseases by a non-invasive test of intraluminal lipolysis using 13 carbon ( 13 C) labelled mixed triglyceride (1, 3-distearyl, 2[ 13 C] octanoyl glycerol). The children with cystic fibrosis without pancreatic supplements had a median (range) 13 C cumulative percentage dose recovered over six hours (cPDR) of 3.1% (0–31.7), the controls 31.0% (21.8–41.1), and the subjects with mucosal disease 27.8% (19.7–32.5). In 23 subjects with cystic fibrosis the usual dose of pancreatic enzyme supplements increased the cPDR to a median of 23.9% (0–45.6), and twice the usual dose of enteric coated microspheres increased the cPDR to 31.1% (11.1–47.8). There was no significant difference between the median cPDR of normal controls and children with mucosal disease, but there was a highly significant difference between these groups and children with untreated cystic fibrosis. Thirteen children with cystic fibrosis had no 13 C recovery in their breath without enzymes and 10 showed marked increases with regular enzymes. In eight children doubling the dose of enzymes caused no or minimal improvement. The mixed triglyceride breath test offers a simple, non-invasive way of assessing the need for pancreatic enzyme supplementation in children with cystic fibrosis and could be used to optimise treatment.